Inovasi Pembelajaran Mata Kuliah Pembelajaran Mikro Berbasis Model PjBL (Project Based Learning) Untuk Meningkatkan Kreativitas Mahasiswa : (Learning Innovation of Micro Learning Courses Based on The PjBL (Project Based Learning) Model to Increase Student Creativity) - Ali Sadikin; Upik Yelianti (BIODIK, 2021)
Good learning is innovative learning following the times. To support the vision and mission of the Jambi Smart University, changes will be made to the micro learning courses in the biology education study program. The change is learning innovation using the PjBL (Project Based Learning) learning model. With this PjBL model, learning tools, teaching materials, and evaluation instruments will be developed to increase student creativity in the Biology Education Study Program, FKIP Jambi University. The research method uses classroom action research (CAR) which is planned for 2 cycles. The stages include: planning, implementation and observation, and reflection. At the planning stage, a small discussion was held between the teaching team and agreed on the implementation of PJBL. At the implementation stage, students make a project in the form of a learning video containing teaching skills. At the observation stage: students are asked to present their project in front of the class virtually, then lecturers and colleagues observe and provide feedback. Finally, the reflection stage, input and comments from lecturers and colleagues are recorded and project improvements are made. In the first cycle, the results of the observation were 55% in the pretty good category. Then improvements were made from input and comments from lecturers and colleagues, so that in the second cycle there was an increase in student creativity at a score of 80% in the good category. Pembelajaran yang baik adalah pembelajaran yang inovatif mengikuti perkembangan zaman. Untuk mendukung visi dan misi Universitas Jambi smart maka mata kuliah pembelajaran mikro di prodi pendidikan biologi akan diadakan perubahan. Perubahan itu adalah inovasi pembelajaran menggunakan model pembelajaran PjBL (Project Based Learning). Dengan model PjBL ini akan dikembangkan perangkat pembelajaran, bahan ajar, dan instrument evaluasi untuk meningkatkan kreativitas mahasiswa di Prodi Pendidikan Biologi FKIP Universitas Jambi. Metode penelitian mengunakan penelitian tindakan kelas (PTK) yang direncanakan 2 siklus. Adapun tahapnnya meliputi: perencanaan, pelaksanaan dan observasi, dan refleksi. Pada tahap perencanaan dilakukan diskusi kecil antar tim pengajar dan disepakati penerapan PJBL. Pada tahap pelaksanaan mahasiswa membuat proyek berupa video pembelajaran yang berisi keterampilan mengajar. Pada tahap pengamatan: mahasiswa diminta untuk mempresentasikan proyeknya tersebut didepan kelas secara virtual, kemudian dosen dan teman sejawat mengamati dan memberikan umpan balik. Terakhir tahap refleksi masukan dan komentar dari dosen dan teman sejawat dicatat dan dilakukan perbaikan proyek. Pada siklus 1 diperoleh hasil pengamatan 55 % kategori cukup baik. Lalu diadakan perbaikan dari masukan dan komentar dari dosen dan teman sejawat maka pada siklus II mengalami kenaikan kreativitas mahasiswa pada skor 80 % dalam kategori baik. Â